Networks, communities and digital culture: innovation by disconnection - Porto Renó, Denis (2018)
The construction of relationship networks was potentiated from the advent of contemporary digital technologies, which made possible the emergence of new "spatial"" conditions and the networked society or even innovation, which can be contemplated processes and technologies. This article presents, based on an in-depth analytical case study, the community Rede das Coisas Simples, carried out in the city of Águeda, in the central region of Portugal, conceived from non-adoption of digital technologies for its mobilization. That's a growing philosophy among young people of digital culture - unplugged. If you wait, with the presentation of this research, build subsidies for new studies on digital culture among young people."